Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Pengemudi Distribusi Produksi di PT Aneka Gas Industri Tbk-Bekasi Tahun 2021 - Lisda Apriliana; Agustina Agustina (Jurnal Persada Husada Indonesia, 2021)
Work fatigue is the result of prolonged mental or physical work that can affect the performance of the workforce and interfere with their mental vigilance and can lead to dangerous faults. Feelings of work fatigue are subjective symptom of work fatigue that workers complain about which are all unpleasant feelings. The purpose of this study was to determine the factors associated with work fatigue on production distribution drivers at PT Aneka Gas Industri, Tbk – Bekasi in 2021. The study used cross-sectional. The data analysis used the chi square test. The sampling method used is accidental with a sample size of 80 drivers. The research instrument used was a fatigue symptom questionnaire sourced from the Industrial Fatigue Research Committee (IFRC). The results showed that 49 people (61.3%) experienced low fatigue and 31 (38.8%) were experienced moderate fatigue. The results of the study obtained variables related work fatigue, namely age p = 0.020 (α < 0.05), physical condition p= 0,028 (α < 0.05), driving duration p = 0.005 (α < 0.05), rest time p = 0.007 (α < 0.05), and the temperature p = 0,000 (α < 0.05). The conclusion from this study is that there is a relationships between age, physical condition, driving duration, rest time and temperatures with work fatigue and there is no relationship between nutrition status, working period and lighting with work fatigue on production distribution drivers at PT Aneka Gas Industri, Tbk – Bekasi 2021. It is recommended for drivers to set working hours to drive and rest for at least 30 minutes after driving for 4 hour. In addition, drivers should drink recommended 8 glasses of water per day to meet the needs of fluids and oxygen in the body.